Fixed Point Iteration Method - Mehmet Karakas (MANAS: Journal of Engineering)
We discuss the problem of finding approximate solutions of the equation x)0 f()0 (1) In some cases it is possible to find the exact roots of the equation (1) for example when f(x) is a quadratic on cubic polynomial otherwise, in general, is interested in finding approximate solutions using some numerical methods. Here, we will discuss a method called fixed point iteration method and a particular case of this method called Newton’s method